The Determination of Exchange Rate, Production Volume, Average Price, and Gross Domestic Product on the Export Value of Indonesian Nutmeg Seeds (HS-090811) to China - Febriyan Athalla Nail Maedy T.; Niniek Imaningsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Indonesia is one of the largest producers and exporters of nutmeg in the world. Nutmeg plays a very crucial role in improving the Indonesian economy. One of the destination countries for nutmeg exports is China. This study aims to determine the factors that influence the Export Value of Indonesian Nutmeg to China. The data in the study were analyzed using a quantitative approach using the Multiple Linear Regression Analysis method. The results of the study indicate that the Exchange Rate has a negative and significant effect on the Export Value of Indonesian Nutmeg Seeds to China, the Amount of Production and Average Price have no effect on the Export Value of Indonesian Nutmeg to China, and China's GDP has a significant positive effect on the Export Value of Indonesian Nutmeg to China.